Reasons to work out at female-only fitness clubs - FRAZÃO, Deimersom Pereira; COELHO FILHO, Carlos Alberto de Andrade (Brazilian journal of physical education and sport, 2015)
This research aims to analize the speech contents of women who work out at female-only fitness clubs, on the grounds of such a practice, with the focus directed to the relationships established between the reasons for this practice and sexual binarism. This is a qualitative study. Based on a semistructured survey, twenty three women attending three female-only fitness clubs located in the city of Juiz de Fora, Minas Gerais, were interviewed. We have concluded that respondents' motivation to work out at female-only fitness clubs was demonstrated to be primarily anchored in the relationship they have, directly or indirectly, with the man at home (boyfriends, husbands) and / or in the social scenery. When compared to mixed gyms, those exclusively for women emerge as a space which can provide women greater freedom to: express their own body dissatisfaction and watch another woman without giving rise to feelings of competitiveness, as usually happens in environments with men around. They also present themselves less subjected to body patterns regarding dress and / or makeup, which are considered to be more beautiful or elaborate, even if by they themselves. Also noteworthy is the possibility that in female-only fitness clubs, women are more focused on the physical drilling, since they feel more at ease, thereby focusing more on the exercises and performing movements / exercises without the constraints caused by men's invasive glances.